PATIENT'S PERSONALITY: AN INTERDISCIPLINARY APPROACH TO CARDIOVASCULAR PATHOLOGY - E. O. Taratukhin (Российский кардиологический журнал, 2014)
The article takes into account the opportunity of the positive health, that is possible instead of the fight against diseases. As a main part of such interdisciplinary approach the personality is evaluated. To summon up the knowledge from biochemical to cultural bodies of human existence might turn medical science from the negation of a somatic disease to the health.